ANALISIS PEMBAKARAN DAN PEMANASAN PADA KOMPOR BIJI JARAK DENGAN BERBAGAI DIAMETER DAN JUMLAH - M. Julian Ginting; R. Mursidi; Edward Saleh (Universitas Sriwijaya, 2012)
Theobjective of this research was to analyze burning and heating on the stove ofjatropha-seeds with various of diameters and sarangan holes, in order to achieve the higher efficiency of the stoveof jatropha-seeds. Thisresearch has been conducted in the machinery and workshop laboratory of TheAgricultural Engineering Program, The Agricultural Technology Department,Agriculture Faculty, Sriwijaya University, Indralaya from April 2011 to October2011. Themethod which is used in this research is block randomized design factorialmethod which consist of two treatment factors and each treatment factor consistof two stages and each treatment combination is repeated three times. The firsttreatment with two stages is the diameter of the sarangan holes (3 mm and 4mm), the second treatment with two stages is the amount of the sarangan holesper cm2 (2 pieces/cm2 and 4 pieces/cm2). The parameter observed include the mainparameters and the supporting parameter. The main parameter is the fuel combustion rate, flame height ,efficiencyof water heating, the rate of water heating, and the supporting parameter includingflame temperature, fuel efficiency, burning time of the jatropha fuels, waterheating time, the difference temperature on the components of the stove. The research result showed the best that sarangancontained on D1X1 with a combination of diameter (3 mm)and the amount of sarangan holes per-cm2 (2 pieces/cm2)with 0,69 kg/jam of combustion rate, 30 cm of flame height, the rate of waterheating 0,1245kkal/s, and the efficiency of waterheating 8,86 %. Keywords :The jatropha-seeds stove, Jatropha-seed fuels, and Sarangan of the jatropha-seedsstove